2022
DOI: 10.1002/adma.202106516
|View full text |Cite
|
Sign up to set email alerts
|

Nanovesicle‐Mediated Targeted Delivery of Immune Checkpoint Blockades to Potentiate Therapeutic Efficacy and Prevent Side Effects

Abstract: Despite the clinically proven efficacies of immune checkpoint blockades, including anti‐cytotoxic T lymphocyte‐associated protein 4 antibody (αCTLA‐4), the low response rate and immune‐related adverse events (irAEs) in cancer patients represent major drawbacks of the therapy. These drawbacks of αCTLA‐4 therapy are mainly due to the suboptimal activation of tumor‐specific cytotoxic T lymphocytes (CTLs) and the systemic nonspecific activation of T cells. To overcome such drawbacks, αCTLA‐4 is delivered by dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…Jung et al developed a biomimetic nanovesicle (αCTLA-4@DCNV-TA) by conjugating αCTLA-4 and tumor antigen to the serial extruded mature DC membrane nanovesicle (DCNV) (Figure 15F). 263 Compared to conventional αCTLA-4 injection therapy, administration with αCTLA-4@DCNV-TAs significantly generated effective tumor-specific CTLs (Figure 15G) to control tumor growth and, most importantly, decrease irAEs in the syngeneic tumor model.…”
Section: Organic Biomaterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Jung et al developed a biomimetic nanovesicle (αCTLA-4@DCNV-TA) by conjugating αCTLA-4 and tumor antigen to the serial extruded mature DC membrane nanovesicle (DCNV) (Figure 15F). 263 Compared to conventional αCTLA-4 injection therapy, administration with αCTLA-4@DCNV-TAs significantly generated effective tumor-specific CTLs (Figure 15G) to control tumor growth and, most importantly, decrease irAEs in the syngeneic tumor model.…”
Section: Organic Biomaterialsmentioning
confidence: 98%
“…(G) Immunomodulation properties of αCTLA-4@DCNV-TA. (F,G) Reproduced with permission from ref . Copyright 2022 Wiley.…”
Section: Biomaterial-assisted Drug Delivery For Enhanced Icb Therapymentioning
confidence: 99%
“…T cell dysfunction caused by persistent antigen stimulation triggers exhaustion. Tim-3 expression and PD-1 expression of T cells have been identified as markers of T cell exhaustion . As a large secondary lymphoid organ, the spleen is the primary site for T cell activation.…”
Section: Resultsmentioning
confidence: 99%
“…Tim-3 expression and PD-1 expression of T cells have been identified as markers of T cell exhaustion. 39 As a large secondary lymphoid organ, the spleen is the primary site for T cell activation. We explored the frequency of exhausted T cells in the spleen and found that the aDCM@ PLGA/RAPA group was a significant decrease in the frequency of PD-1 + TIM3 + CD8 + T cells compared with other groups (Figure 4H,I), indicating that tumor-infiltrating T cells can exert more antitumor effects.…”
Section: Enhanced Dcs Maturation and T Cell Activation Mediated By Ad...mentioning
confidence: 99%
“…It is well-known that MSCs promote the proliferation and angiogenesis of endothelial cells, exert anti-inflammatory effects by polarizing microglia from pro-inflammatory M1 microglia to anti-inflammatory M2 microglia, and stimulate astrocytes to express neurotrophic, antiapoptotic, and angiogenic factors. , First, we evaluated the angiogenic efficacy of MSC-IONPs by a capillary tube formation assay using cocultures of human umbilical vein endothelial cells (HUVECs) and MSCs in a trans-well system. In the IONP-treated groups, an amount equal to the amount of IONPs contained in the MSC-IONPs was added.…”
mentioning
confidence: 99%